2005
DOI: 10.1515/cclm.2005.191
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and B vitamins in mild cognitive impairment and dementia

Abstract: Elderly subjects with mild cognitive impairment have a high risk for conversion to Alzheimer's disease or are already in a preclinical dementia stage. By cross-sectionally comparing subjects in prodromal and early phases of dementia with non-demented controls, we tested the hypothesis whether low serum vitamin B12 and folate and high plasma total homocysteine concentrations precede or are a consequence of dementia onset. From a large population of 623 consecutive subjects seen at the Memory Clinic (Ospedale Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
138
1
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(155 citation statements)
references
References 20 publications
10
138
1
6
Order By: Relevance
“…Since hyperhomocysteinemia is suspected as being a risk factor for many diseases (oral clefts, Down syndrome, placenta-mediated diseases, colorectal neoplasias, Alzheimer's disease, etc.) in addition to vascular diseases and neural-tube defects (Ray and Laskin 1999;Ames 1999;Botto and Yang 2000;Ueland et al 2001;Ames et al 2002;Quadri et al 2004), this information is useful not only for the prevention of atherosclerosis but also for that of other diseases when considering a tailormade preventative approach.…”
Section: Discussionmentioning
confidence: 99%
“…Since hyperhomocysteinemia is suspected as being a risk factor for many diseases (oral clefts, Down syndrome, placenta-mediated diseases, colorectal neoplasias, Alzheimer's disease, etc.) in addition to vascular diseases and neural-tube defects (Ray and Laskin 1999;Ames 1999;Botto and Yang 2000;Ueland et al 2001;Ames et al 2002;Quadri et al 2004), this information is useful not only for the prevention of atherosclerosis but also for that of other diseases when considering a tailormade preventative approach.…”
Section: Discussionmentioning
confidence: 99%
“…Studies confirm that a lack of vitamin B12 is an important risk factor of dementia. Low levels of vitamin B12 in serum is associated with an increased risk of AD and MCI (Quadri et al, 2004). In the healthy elderly population, the levels of vitamin B12 in serum are positively related to cognitive ability (Duthie et al, 2002).…”
Section: The Influence Of Gut Microbiota On Neurochemical and Metabolmentioning
confidence: 99%
“…Its beneficial effects on the function of this system is associated with its participation in the formation of neuro-stimulating substances in the body such as dopamine, norepinephrine and epinephrine (Paul et al 2004, Coppen & Bolander-Gouaille 2005, Reynolds 2006). Many clinical and epidemiological studies have shown that folate deficiency in the diet leads to a number of neuropsychiatric disorders such as depression, psychosis, dementia and seizures (Quadri et al 2004, Luchsinger et al 2007.…”
Section: Importance Of Folates For the Human Nutritionmentioning
confidence: 99%